2019
DOI: 10.1096/fj.201802758rrr
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intracranial hemangioma growth and hemorrhage by TNFSF15

Abstract: Hemangioblastoma (HB) is an abnormal intracranial buildup of blood vessels that exhibit a great potential for hemorrhage. Surgical options are limited, and few medications are available for treatment. We show here by immunohistochemical analysis that HB lesions display highly increased levels of VEGF expression and macrophage/microglia infiltration compared with those in normal brain tissues. In the meantime, TNF superfamily 15 (TNFSF15) (also known as vascular endothelial growth inhibitor), an antiangiogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…To determine the impact of TNFSF15 on early brain injury in ICH, we set-up an ICH model by intracranial injection of collagenase into the ipsilateral hemispheres of TNFSF15-overexpressing transgenic mice (SPC-TNFSF15) ( Yang et al, 2019 ) and their transgene-negative littermates. We measured the ICH lesion volume with Luxol fast blue/cresyl violet staining on day 3 postinjury, and found that the lesion volumes in the TNFSF15 group were about 50% of those in the littermates ( Figure 1A and B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine the impact of TNFSF15 on early brain injury in ICH, we set-up an ICH model by intracranial injection of collagenase into the ipsilateral hemispheres of TNFSF15-overexpressing transgenic mice (SPC-TNFSF15) ( Yang et al, 2019 ) and their transgene-negative littermates. We measured the ICH lesion volume with Luxol fast blue/cresyl violet staining on day 3 postinjury, and found that the lesion volumes in the TNFSF15 group were about 50% of those in the littermates ( Figure 1A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…It is plausible that TNFSF15 actions contribute to the reduction of the extent of inflammation in the acute phase of ICH. Decreased leukocyte recruitment after TNFSF15 treatment has been observed in three different brain disease models, including collagenase-induced ICH, intracranial hemangioma ( Yang et al, 2019 ), and TBI ( Gao et al, 2015 ). VEGF is known to induce macrophage/microglia activation and migration to an inflammation site via VEGFR1 on macrophage/microglia ( Kerber et al, 2008 ) and to recruit MMP-9 expressing neutrophils ( Christoffersson et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations